Protentions and Retentions of Xenakis and Cage: Nonhuman Actors, Genre and Time in Microsound. - Haworth, Christopher (Contemporary Music Review)
This article takes an actor-network theory approach to the elusive genre of microsound. The aim is twofold: to demonstrate what ANT's sociology of associations can offer to the study of music, and to consider what aspects would need to be rethought in order for ANT to represent a credible approach to art histories and genres. The ANT analysis traces two lines of inheritance in microsound: a 'weak' line associated with 'quiet' or 'small' sounds, and with strong links to John Cage; and a 'strong' line associated with microtime, sonic materialism, and the 'granular paradigm', for which Iannis Xenakis is the primary antecedent. Through an analysis of the processes involved in reinforcing and attenuating these strong and weak lines of inheritance, some absences in ANT's analytics of mediation are identified concerning temporal mediation. The last section of the article turns to the theorisation of time and genre found in Georgina Born's extension of the work of Alfred Gell and to Michel Foucault's account of authorship to analyse the bidirectional mediation of art and music corpuses, genres and genealogies as they extend through time.